Strategi Kepala Sekolah dalam Pelaksanaan Manajemen Pendidikan yang Berbasis Keislaman di SMA Al Fattah Sidoarjo - Muhamad Pian Maulana; M. Athoiful Fanan (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This research aims to describe and analyze school principals' strategies in implementing Islamic-based education management through strategy formulation, strategy implementation, strategy evaluation, this research approach uses qualitative research with descriptive research type. The subjects of this research were school principals and heads of curriculum who were selected using purposive sampling. Data collection techniques include observation, interviews and documentation. Data analysis uses the Miles, Huberman and Saldana model, namely data condensation, data presentation, and drawing conclusions or verification. The results of the research show that: 1) the principal's strategy in implementing Islamic-based education management is through strategy formulation which begins with formulating a vision and mission, SWOT analysis, determining a strategy then implementing it in the form of a superior program and conducting an evaluation. they use inputs, processes and benchmarks. output. 2) The supporting factors for implementing the principal's strategy are in the form of support for infrastructure, while the inhibiting factors are financial aspects and lack of student discipline.